ANALYSIS OF THE PERFORMANCE OF THE SAMARINDA CITY DPRD FOR THE 2014-2019 PERIOD IN MAKING LOCAL REGULATIONS - Pajar Pahrudin; Kusnandar; M.Raihan Ramadhan (Media Inovasi Pendidikan dan Publikasi, 2023)
The purpose of this study was to analyze the performance of the Samarinda City DPRD for the 2014-2019 period in drafting regional regulations. The research method uses a qualitative approach through data collection instruments of interviews, observation, and documentation while the informant selection technique is snow ball sampling. The data analysis techniques in this study used the stages of reduction, verification and conclusion. The research analysis was carried out based on the dimensions of responsiveness, responsibility and accountability. The results of the study show that the performance of members of the East Kalimantan Provincial DPRD for the 2014-2019 period in drafting regional regulations is still not fully effective, especially the dimensions of responsiveness and accountability, while the dimensions of responsibility have been running effectively. This has had an impact on the delays in various local government programs and the not yet optimal handling of public complaints. The recommendation of this research is to encourage public participation, especially in drafting regional regulations so that they can improve the performance of DPRD members, especially in the dimensions of responsiveness and accountability.